LOBAR DISTRIBUTION OF CORTICAL GREY MATTER LESIONS IN MULTIPLE SCLEROSIS CLINICAL SUBGROUPS. Issue 11 (9th October 2013) - Sethi, Varun; Yousry, Tarek A; Muhlert, Nils; Tozer, Daniel; Ron, Maria; Golay, Xavier; Wheeler–Kingshott, Claudia; Miller, David H; Chard, Declan T
Abstract : Background: Cortical grey matter lesions (CGM) in MS are associated with cognitive impairment and progressive disability. 1 2 Histopathology studies have shown a predominantly fronto–temporal cortical lesion location, 3 but these are based mainly on post mortem study of patients with end stage progressive MS. The phase sensitive inversion recovery (PSIR) MRI sequence is sensitive in detecting MS CGM lesions in vivo, 4 and thus has potential to characterise their regional distribution in patients with both relapsing remitting and progressive MS. Aim: To study the lobar distribution of CGM lesions and their relationship to clinical course. Methods: Thirty MS patients [16 Relapsing remitting (RR), 9 primary progressive (PP) and 5 (SP) MS] were scanned using a Philips 3T Achieva system. PSIR scans (0.5×0.5×2 mm) were acquired. CGM lesions were divided into intracortical (IC, only involving cortex) and leucocortical (LC, mixed GM–WM lesions). Lobar lesion counts were determined in the frontal, parietal, temporal, occipital and insular lobes. For this NiftyReg ((http://sourceforge.net/projects/niftyreg) was used to register the MNI 152 brain template to each participants' PSIR image in a series of steps. 1) A study–specific T1–weighted template was generated by iteratively registering each participants' T1 image together to a common image, with repeated iterations. 2) the MNI template was nonlinearly registered to this T1–template. 3) the T1–template was nonlinearly registered to each participants' T1–weighted image. 4) the T1–weighted image was rigidly registered to the PSIR image for each participant 5) The transformation parameters from steps 2 to 4 were combined and used to transform the lobar parcellations from the Oxford–Harvard atlas into each participants' PSIR space. 6) A maximum likelihood algorithm was then used to remove any overlap between the parcellations in PSIR space. The number and volume of lesions falling within each parcellation was measured based on lesion–type. Multivariate ANOVA was performed using patient type as the fixed grouping factor. Results: In the whole MS cohort, the mean number (±standard deviation) of CGM lesions (IC+LC) was 7.7±5.1, 7.4±5.8, 5.1±3.6, 0.9±1.7 and 2.1±1.8 in the frontal, temporal, parietal, occipital and insular regions. The total volume of lesion was 0.3±0.2, 0.2±0.2, 0.1±0.08, 0.01±0.02 and 0.09±0.1 (in cc) in these regions respectively. No preferential regional distribution of lesions was noted among the clinical subgroups. Conclusions: Using PSIR at 3T, lesions involving CGM were visible in all lobes. A higher number of CGM lesions were noted in the frontal and temporal lobes both relapsing remitting and progressive MS subgroups. Occipital CGM lesions were uncommon.